Experimental and numerical investigation of UIC 54 rail degradation. (April 2020) - Belalia, A.; Kamla, Y.; Amara, M.; Meliani, M. Hadj; El Azizi, A.; Azari, Z.
Abstract: Rolling contact fatigue has a significant impact on the service life of the infrastructure, in particular on the rail, which undergoes various defects, the severity of which threatens transport safety. Our study focused on the investigation of a curved track on the Algerian railway network laid in the 1980s by checking the design, the rail material, and the operating conditions of the track, and then the degradation of the rail for a classification and defect analysis based on standards. The methodology used consists of a visual field study using conventional measurement methods, supported by on-site and laboratory ultrasonic inspection to highlight the severity of defects for railway safety and to measure the effectiveness of the operator's maintenance policies, which must be improved in terms of defect's detection and removal to extend the infrastructure's life.